URGENSI PENERAPAN PRINSIP EKSTRATERITORIAL BAGI PENEGAKKAN HUKUM PERSAINGAN USAHA DI INDONESIA (Lex Jurnalica, 2021)
ABSTRACTThe purpose of this paper is to study and analyze the importance of applying extraterritorial principles for the enforcement of business competition law in Indonesia, which in the era of globalization of cross-border business activities will be easier, faster, and more efficient. While regulating the law shifts to the development of business transactions. This study uses normative juridical methods and involves secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The results of this study indicate that ther is an urgency to apply extraterritorial principles, namely, the existence of business development by businesses through E-commerce that will influence and enter the market in Indonesia. In Batam, the Riau Archipelago province has carried out anti-competitive practices which cannot be achieved by law enforcement due to the application of territorial principles. The application of extraterritorial principles is also commonly used in the formation of law in Indonesia. While in the United States the effect doctrine has been applied in the Sherment Act and India has applied the extraterritorial principle in 32 The Competition Act.